New Light on the History of Isaac Newton's Library. (17th March 2020) - Thomson, Karen
Abstract: In the standard scholarly work, The Library of Isaac Newton published by CUP in 1978, John Harrison makes two significant assumptions about the library's early history which are incorrect. This paper highlights the necessary revisions, including the unnoticed role played by Mrs Jane Musgrave, Jane Austen's godmother, in the library's preservation. It also proposes for the first time a plausible reason why John Huggins, Warden of the Fleet Prison, bought the library from the executors immediately after Newton's death.